90.6k views
21 votes
4r + y = 23
3x - y= 12

User Eixcs
by
5.0k points

2 Answers

8 votes

Answer:

7x = 35

Explanation:

User Jalakoo
by
5.2k points
8 votes

9514 1404 393

Answer:

(x, y) = (5, 3)

Explanation:

We presume your two equations are ...

  • 4x + y = 23
  • 3x - y = 12

The coefficients of y are opposites, so we can add these equations to eliminate y:

(4x +y) +(3x -y) = (23) +(12)

7x = 35

x = 5

Substituting into the second equation, we get ...

3(5) -y = 12

y = 15 -12 = 3

The solution is (x, y) = (5, 3).

4r + y = 23 3x - y= 12-example-1
User Torsten Ojaperv
by
5.3k points